Replacement of corn with pre-dried cassava root silage in the diet for dairy goats - Silva, Maria Josilaine Matos dos Santos; Silva, Edneide Rodrigues da; Santos, Fátima Lira dos; Santos, Cinthya Mikaelly da Silva; Cavalcante, Paulo Otávio Silva; Pereira, Kedes Paulo; Almeida, Vitor Visintin Silva de; Lima Júnior, Dorgival Morais de (Acta Scientiarum. Animal Sciences, 2022)
The objective of this study was to evaluate the effect of replacement of corn with pre-dried cassava root silage (CRS) on intake, ingestive behavior, production and composition of goat milk. Five lactating Saanen goats were used, with 42.5 ± 4.2 kg body weight and production of 2 kg milk day-1, distributed in a 5 x 5 Latin square with five treatments: 0, 28.6, 58.0, 81.6 and 100% replacement of corn with CRS in the diet dry matter. Goats were monitored for five periods of 15 days each. The intake of dry matter, crude protein and neutral detergent fiber decreased linearly (p <0.05) with the replacement of corn with CRS. Feeding (348.5 ± 62.1 min.) and rumination (468.8 ± 83.8 min.) times were not influenced (p >0.05) by the replacement of corn with CRS, but the ingestion and rumination efficiencies had a linear increase (p > 0.05). Milk production (2.17 ± 0.45 kg day-1), fat (3.49 ± 0.42%), protein (3.11 ± 0.13%) and lactose (4.47 ± 0,11%) of goat milk were not influenced (p >0.05) by the replacement of corn with CRS. Therefore, it is recommended the total replacement of corn with pre-dried cassava root silage in the diet for dairy goats with an average production of 2 kg day-1.